Trends of cutaneous basal cell carcinoma, squamous cell carcinoma, and melanoma among the Chinese, Malays, and Indians in Singapore from 1968-2016Capsule Summary - Choon Chiat Oh, MBBS, MSc; Aizhen Jin, MSc; Woon-Puay Koh, MBBS, PhD (Elsevier, 2021)
Background: Previous analysis showed that the incidence rates of skin cancer in Singapore increased from 1968 to 2006, especially among older Chinese, and particularly for basal cell carcinoma (BCC). Objective: We updated the skin cancer incidence rates and time trends among the Chinese, Malays, and Indians in Singapore. Methods: We analyzed the skin cancer incidence from the nationwide Singapore Cancer Registry from 1968 to 2016. Results: Among 12,692 cases diagnosed from 1968 to 2016, there were 8367 (65.9%) cases of BCC, 3598 (28.3%) of squamous cell carcinoma (SCC), and 727 (5.8%) of melanoma. The mean ages at skin cancer diagnosis were 72.7 years for SCC, 66.9 years for BCC, and 59.8 years for melanoma. Sun-exposed areas accounted for 81.3% of BCCs, 61.6% of SCCs, and 26.7% of melanomas. The age-standardized incidence rate of cutaneous BCC was highest in the Chinese and increased by 2.5 fold over the study period, followed by a lower rate and slower increase in the Malays, and the lowest rate among the Indians. The SCC and melanoma incidences remained low in all 3 ethnicities during this study period. The Chinese had the highest relative risk for developing any skin cancer (P < .0001) compared with those of the Malays and Indians. Most cases of skin cancer were diagnosed at age ≥60, with men showing a higher incidence of SCC compared with that of women. Conclusion: Incidence rates of BCC have increased in Singapore, especially among the Chinese, in the past 5 decades. The SCC and melanoma incidence rates remained low and stable.